Running 5K and 10K a training guide - Chalfen, David (The Crowood Press, 2014)
An accessible, jargon-free guide for all distance runners committed to improving their times. It doesn't offer any quick and easy answers; just tried-and-tested practical advice on how to train more effectively and shave a few seconds - or even minutes - off your personal best." --Back cover